AB1054 Diagnostic Musculoskeletal Ultrasound (MSK-US) Use Lags MSK-MRI Utilization in USA. (9th June 2015) - Kaeley, G.; Monticalvo, D.; Smotherman, C.; Lukens-Bull, K.; Dodani, S.
Abstract : Background: MSK-US use has rapidly adapted in the USA as an effective means of diagnosing and treating MSK pathologies by several MSK providers. Recent studies have highlighted increasing MSK-US utilization by non-radiologists, surpassing radiologists, and this growth been a major cost driver for insurance companies, including Medicare, the government's funded healthcare system for elderly. 1 However estimation and comparison of the utilization of diagnostic MSK-US and MSK-MRI services by providers will help Medicare with efficient services provision in a cost-effective manner Objectives: To examine the relative utilization of diagnostic MSK-US and MSK-MRI amongst MSK specialties billing Medicare in the USA Methods: Source data were obtained from the Medicare publically available online data file. For purposes of tabulating volume and descriptives on utilization, non-duplicative billing claims for MSK-US and MSK-MRI were calculated by practitioner specialty. Similarly, non-duplicative counts for providers of these services were also performed. Total number of providers was obtained from the file, whereas records on specific MSK-US and MSK-MRI were extracted and separate descriptive summary analysis was performed using SAS 9.4 ® (Cary, NC). MSK-US billing requires separate diagnostic MSK-US and MSK-MRI that were used for analysis. We analyzed 2012 annual volume (utilization) by provider type using specialties, practice settings, and geographic regions (US states) where the studies were performed Results: Table provides 2012 Medicare utilization data. Providers and service counts for both diagnostic MSK-US and MSK-MRI are calculated for each provider specialty with the total number of providers and services respectively. As shown in the table, comparing the total MSK services submitted, Radiologists were responsible for 90% of the MSK-MRI and 36% of the diagnostic MSK-US billing. Amongst non-radiologists, Orthopedic specialists were responsible for 9% and 12% of the MSK-MRI and diagnostic MSK-US billing respectively, whereas Rheumatologists billed 1% MSK-MRI and 15% of diagnostic MSK-US services. When analyzing the proportion of providers billing MSK-MRI services, the majority of services were billed by radiologists and orthopedic specialists and MSK-MRI utilization far outstripped diagnostic MSK-US use Conclusions: This study presents novel and striking findings on MSK-MRI providers and services, with orthopedic specialists among the non-Radiology group as the highest utilizers for MSK-MRI compared to diagnostic MSK-US. Diagnostic US can aid in the management of MSK conditions and may substitute for MRI in many circumstances. We conclude that the relative use of diagnostic MSK-US is low and MSK-MRI use still predominates leading to the high cost to Medicare in the USA References: Sharpe RE, Nazarian LN, Parker L, et al. Dramatically increased MSK-US utilization from 2000 to 2009, especially by podiatrists in private offices. JACR. 2012;9(2):141-6. Disclosure of Interest: None declared